Robust decentralized approach to interaction mitigation in VSC-HVDC grids through impedance minimization. (January 2022) - Agbemuko, Adedotun J.; Domínguez-García, José Luis; Gomis-Bellmunt, Oriol
Abstract: An interconnection of independently designed voltage source converters (VSCs) and their control in high voltage DC grids can result in network-level detrimental interactions and even instability. In many cases, vendors are not willing to share proprietary information about their designs in a manner that allows the entire system to be designed considering the collective dynamics. Besides, such an endeavour is not realistic. In this paper, robust network-level global controllers are proposed to decouple interacting VSCs through an impedance shaping technique. Particularly, the global controllers are designed without any need to establish the internal controller structure of any VSC which is often proprietary. Rather, the global controllers rely on the externally measurable feedback impedance of each VSC in stand-alone and the rest of the system. It is demonstrated how robust convex optimization framework can be exploited to robustly shape global feedback impedances to obtain a decoupled network. The synthesized controllers are validated through nonlinear simulations of the physical model. Highlights: Impedance-based robust global controllers to decouple interconnected HVDC converters. Impedance-based analysis of interaction mechanism in multi-vendor VSC-HVDC grids. Improved tolerance, global stability, and disturbance rejection in VSCHVDC networks. Demonstration of modularity and scalability of designed global controllers.